A Comparative Study of Marriage Agreements Between Cross-National Couples in Indonesia and the Netherlands - Rizqareka D, Cinta; Afifa, Erina Nur; Busroni, Rania Syifa; Fazila, Raysha Aulia; Akbar, Muhamad Dafi; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2026)
Marriages between Indonesian citizens and foreign nationals create complex legal consequences, particularly regarding the regulation of joint property and the legal status of the parties involved. A prenuptial agreement serves as an essential legal instrument to provide legal certainty and protection for the rights and obligations of both spouses. This study aims to analyze the differences in the regulation of prenuptial agreements for couples with different nationalities between Indonesia and the Netherlands, as well as to examine their implications for the recognition and enforcement of such agreements in both countries. The research employs a normative juridical method with statutory and comparative approaches, using primary legal materials such as the Indonesian Civil Code and the Dutch Burgerlijk Wetboek, along with secondary materials including legal literature and academic journals. The findings reveal that Indonesia still applies the joint property system as the default rule under Law Number 1 of 1974 on Marriage, whereas the Netherlands, since 2018, has adopted the limited community of property system, which establishes the separation of personal property as the legal foundation. Moreover, the Netherlands grants couples with different nationalities the freedom to choose the applicable law through the choice of law mechanism as regulated in Council Regulation (EU) No. 2016/1103, while Indonesia does not yet have a clear mechanism in this regard. These differences have implications for legal certainty, regulatory flexibility, and the protection of spousal rights in mixed marriages